Impacts caused by COVID-19 on the Brazilian Education sector: A descriptive analysis (Research, Society and Development, 2020)
More than 51 years ago the world did not live in such a frightening reality and with a high number of deaths, caused by a pandemic, as we currently live with Covid-19. Covid-19 emerged in China in December 2019, when there were reports of a respiratory infection caused by a new coronavirus, SARS-CoV-2 (WU, Di; et al. 2020). The disease can be transmitted through the handshake, saliva droplets and contaminated objects or surfaces (Ministry of Health, 2020.). As a consequence of being highly contagious, it caused the closing of stores of non-essential services, including schools and universities. The purpose of this project is to analyze the impacts caused by Covid-19 on education in Brazil, in order to compare the different consequences in the Public and Private education network. Descriptive statistics techniques will be used to describe and summarize the data, obtained through the Form that was sent to teachers and students, and hypothesis tests to affirm or deny some hypotheses that will be raised throughout this article.